2020
DOI: 10.20885/jkki.vol11.iss1.art4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing tools of balance tests in assessing balance of middle-aged women with or without exercises

Abstract: Background: Fall risks among middle-aged women are relatively high. However, there is a lack of studies on tools of balance tests and their accuracy among middle-aged women. Objective: The aim of this study is to compare three tools of balance tests to predict falls of middle-aged women who exercise regularly and who do not. Methods: Eighty-five middle-aged women (50-64 years old) were included in this study, and 40 women of them (47.1%) exercised regularly. The Berg Balance Scale (BBS), Timed Up and Go Test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A higher score of the m30STS indicates a greater lower extremity strength. 11,15 This test rarely causes fatigue because it only takes 30 sec and is based on the patient's ability. 10,16,17 Furthermore, the m30STS indirectly evaluates the cardiorespiratory fitness, evidenced by a moderate to strong positive correlation with the 6MWT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A higher score of the m30STS indicates a greater lower extremity strength. 11,15 This test rarely causes fatigue because it only takes 30 sec and is based on the patient's ability. 10,16,17 Furthermore, the m30STS indirectly evaluates the cardiorespiratory fitness, evidenced by a moderate to strong positive correlation with the 6MWT.…”
Section: Discussionmentioning
confidence: 99%
“…In the healthy elderly, a higher score of m30STS indicated better physical fitness, greater ability to perform the out-of-bed mobilization, especially walking, and could predict fall or recurrent fall incidence. 5,10,11 recurrent fall risks during the out-of-bed mobilization (r = −0.30, p = 0.03). However, all subjects in our study showed a good tolerance of the m30STS, characterized by the absence of desaturation state (SaO 2 <90%), no increased heart rate exceeding the danger threshold (>150 times/min), and no fall incidence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations